Evolution of Inequality in Nigeria: A Tale of Falling Inequality, Rising Poverty and Regional Heterogeneity - John Chiwuzulum Odozi; Ruth Uwaifo Oyelere (Institute of Labor Economics (IZA), 2022)
Recent research on Nigeria indicates declining income inequality. In contrast, anecdotal evidence suggests that only the upper class has benefited from economic growth in Nigeria over time. The disconnect between these findings and anecdotal evidence, and the limitation in how inequality was estimated in the past literature are the motivation for our research. First, we consider if inequality decreased in Nigeria between 2010 and 2018. We then explore how changes in inequality relate to changes in consumption and poverty. In addition, we examine whether there has been convergence in inequality and consumption across regions over this period. Our last question is focused on identifying the sources/factors contributing to inequality in Nigeria over time. Leveraging data from the four waves of the Nigeria General Household Panel Survey (GHS) and carefully measuring inequality using consumption expenditure, our results suggest that inequality has decreased and median consumption expenditure increased. At the same time, poverty incidence and severity increased precipitously. Our findings suggest convergence in estimated inequality by regions but we do not find evidence of convergence across regions in consumption or poverty levels. We also find that durable goods expenditures are the biggest contributor to inequality across expenditure sources. Finally, our results suggest that education and living in an urban area are significant contributors to inequality but their effects have declined over time.
Keywords: D31; I32; O15; O10; 330; inequality; Gini; Nigeria; income distribution; poverty; regional disparities